Astma pri otroku in zdravstvena vzgoja - Jukić Petrovčič, Jasna (Obzornik zdravstvene nege, 1998)
The article describes asthma itself, the contens of health-teaching education and the importance of collaboration between health professionals The article emphasizes self-management of clients, especially their role in the arrangement of their living environment.
Keywords: asthma; astma; child; nega bolnika; otroci; zdravstvena vzgoja